Composição e gelatinização do amido na resposta biológica do jundiá (Rhamdia quelen) - Pedron, Fabio de Araújo (2010)
Fish use carbohydrates less efficiently than proteins for energy production. Even so, the use of such source in the diet may reduce the catabolism of proteins and lipids for energy purposes. The objective of this study was to evaluate growth, metabolism and digestibility of nutrients with different proportions of amylose:amylopectin and thermal processing of starch in the diet of jundiá (Rhamdia quelen). Two completely randomized experiments were conducted, where jundiás were reared in water re-use system consisting of 12 units of 280L and 6 conical units of 200L (digestibility). In the first experiment three diets were tested for 60 days varying in proportions of amylose:amylopectin: P26:74 = 26% amylose and 74% amylopectin, P16:84 = 16% amylase and 84% amylopectin and P0:100 = 0% amylose and 100% amylopectin. The variation of amylose content of the diets did not affect growth, yield, body composition of fish or starch digestibility. For the biochemical variables, less quantity of amylose (P0:100) provided greater mobilization of triglycerides, decrease in the deposition of liver glycogen and increase in metabolism of amino acids and lactate in muscle, indicating gluconeogenesis. The glycemic response of fish was stable (linear, r2 = 0.67) with more amylose (P26:74). Starch with more amylopectin presented quadractly effect P16:84 (r2 = 0.76) and P0:100 (r2 = 0.93). In the second experiment, in a 2X2 factorial arrangement, diets were evaluated with two proportions of amylose:amylopectin and two physic starch forms, raw and gelatinization starch. The fish (14.3±0.6 g) were fed twice a day (4% body weight/day). The proportion of amylose:amylopectin did not affect the growth of jundiá, however, the gelatinization of the starch decreased growth, a higher hepatosomatic and lipid index in body composition of fish. The digestibility of the dry matter and starch was higher with starch gelatinized in the diet. Greater amount of amylopectin and the effect of gelatinization increased serum triglyceride levels. In liver tissues, higher levels of amylose and the process of gelatinization caused greater deposition of glycogen and amino acids. In conclusion, the proportion of amylose:amylopectin is not i change the digestibility of starch and the growth of jundiá, but the increase in amylose provided lower lipid mobilization and stable glycemic levels. The gelatinization of the starch decreased growth and increased the starch digestibility and deposition of body lipids.